Scottish tradition : a collection of Scottish folk literature - Buchan, David, 1939- (Routledge library editions. Folklore ;, 2015)
Scottish folk literature is characterised by a wide range of creative expression: story, song, play and proverb. This anthology, first published in 1984, provides an authoritative introduction to Scottish folk literature, and is unique in that it deals with all the genres intrinsic to Scottish tradition. Its selected texts offer an unusual and diverse enjoyment to the reader, including such forms as wonder tales or Märhcen, classical ballads, riddles, jocular tales, lyric and comic and occupational folksongs, rhymes, historical and supernatural legends, and guisers' plays. The texts chosen cov.